2018
DOI: 10.3390/molecules23123093
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Aurantio-Obtusin from Seed of Cassia obtusifolia L. through Modulation of the NF-κB Pathway

Abstract: Aurantio-obtusin, an anthraquinone compound, isolated from dried seeds of Cassia obtusifolia L. (syn. Senna obtusifolia; Fabaceae) and Cassia tora L. (syn. Senna tora). Although the biological activities of Semen Cassiae have been reported, the anti-inflammatory mechanism of aurantio-obtusin, its main compound, on RAW264.7 cells, remained unknown. We investigated the anti-inflammatory effect of aurantio-obtusin on lipopolysaccharide- (LPS)-induced RAW264.7 cells in vitro and elucidated the possible underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Rhein, chrysophanol, and aurantio-obstusin were identified from Semen Cassiae. Studies highlight their effects on improving insulin secretion (Du et al, 2012), enhancing insulin-dependent glucose transport (Lee and Sohn, 2008), anti-oxidative, anti-hypertension, anti-mutagenic, anti-genotoxic, anti-allergic, and neuroprotective effects (Hou et al, 2018). Hyperoside, astragalin, quercetin, isoquercitrin, and kaempferol were all identified from Semen Cuscutae.…”
Section: Discussionmentioning
confidence: 99%
“…Rhein, chrysophanol, and aurantio-obstusin were identified from Semen Cassiae. Studies highlight their effects on improving insulin secretion (Du et al, 2012), enhancing insulin-dependent glucose transport (Lee and Sohn, 2008), anti-oxidative, anti-hypertension, anti-mutagenic, anti-genotoxic, anti-allergic, and neuroprotective effects (Hou et al, 2018). Hyperoside, astragalin, quercetin, isoquercitrin, and kaempferol were all identified from Semen Cuscutae.…”
Section: Discussionmentioning
confidence: 99%
“…It was firstly used as the quality standard of Cassiae semen in 2010 edition of Chinese Pharmacopoeia, and the content of aurantio-obtusin in Cassiae semen should not be less than 0.080%. At present, the research of aurantio-obtusin is mainly focused on its anti-inflammatory effect ( Hou et al., 2018 ; Kwon et al., 2018 ), and there is little toxicological evaluation on aurantio-obtusin. Anthraquinones are the main active components of Cassiae semen, mainly including rhein, emodin, aloe-emodin, chrysophanol, physcion, chryso-obtusin, obtusifolin, obtusin, and aurantio-obtusin ( Xie et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obtusifolin and gluco‐obtusifolin were shown to inhibit the activities of α‐glucosidases (IC 50 obtusifolin: 142.12 μM; gluco‐obtusifolin: 23.77 μM; Jung et al, ). Hou et al () have reported that aurantio‐obtusin attenuated cytokine‐induced pancreatic β‐cell damage in RAW264.7 cells. Jang et al () have reported the potential of aurantio‐obtusin to inhibit aldose reductase activity with IC 50 value of 13.6 μM.…”
Section: Resultsmentioning
confidence: 99%